Relationship between renal CD68+ infiltrates and the Oxford Classification of IgA nephropathy - Soares, M.; Genitsch, V.; Chakera, Aron; Smith, A.; MacEwen, C.; Bellur, S.; Alham, N.; Roberts, I. (2019)
Aims: The Oxford Classification E score (endocapillary hypercellularity) predicts renal functional decline in IgA nephropathy (IgAN) patients free from steroid/immunosuppressive (IS) therapy, but is poorly reproducible. We hypothesise that endocapillary hypercellularity reflects glomerular inflammation and that the presence of CD68-positive cells is a more robust marker of E score. Methods and results: CD68-positive cells were quantified in glomeruli and tubulointerstitium in biopsies from 118 IgAN patients, and cell counts were correlated with the criteria of the Oxford Classification, assigned on PAS-stained serial sections. There was a strong correlation between median glomerular CD68 count and the percentage of glomeruli showing endocapillary hypercellularity (r = 0.67; P < 0.001; r2 = 0.45), while there was no correlation between CD68-positive cells and mesangial hypercellularity, % segmental sclerosis, % of crescents and % tubular atrophy/interstitial fibrosis (TA/IF). ROC curve analysis demonstrated that a maximum glomerular CD68 count of 6 is the best cut-off for distinguishing E0 from E1 (sensitivity 94.1%, specificity 71%, area under the curve = 89%). Identification of biopsies with a maximum glomerular CD68-count >6 was reproducible (kappa score 0.8), and there was a strong correlation between glomerular CD68 counts obtained by conventional light microscopy and by image analysis (r = 0.80, r2 = 0.64, P < 0.0001). Digital image analysis revealed that tubulointerstitial CD68-positive cells correlated moderately with % TA/IF (r = 0.59, r2 = 0.35, P < 0.001) and GFR at the time of biopsy (r = 0.54, r2 = 0.29, P < 0.0001), but not with mesangial and endocapillary hypercellularity. Conclusions: While glomerular CD68-positive cells emerge as markers of endocapillary hypercellularity, their tubulointerstitial counterparts are associated with chronic damage.